METHODS AND LINGUISTIC GAMES AS A MEANS OF FORMING A FOREIGNER’S COMMUNICATIVE PERSONALITY WHEN TEACHING RUSSIAN AS A FOREIGN LANGUAGE - Kamola Abdullayevna Shokarimova (European Science Publishing, 2024)
This article, based on theoretical and practical experience, describes methods of providing a comfortable teaching of a foreigner, and also reveals the features of the concept of linguistic games, as one of the options and means of forming a communicative personality of a foreigner.
Keywords: linguistic game, inofon, communicative personality, inoculture, RFL.